Hypoglycemic effect of Irvingia gabonensis (Aubry-Lacomate Ex. Ororke), Baill in Type 2 Diabetic Long-Evans Rats (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Irvingia gabonensis (Aubry-Lacomate Ex. Ororke), Baill (African wild mango/bush mango) seeds are   widely used in cooking as a sauce in Cameroon and in most parts of tropical Africa for the treatment of a number of ailments. In this study normal rat food was incorporated with I. gabonensis seed powder (10%) and oil free seed powder (5%) and their chronic effects on streptozotocin induced Type 2 diabetic rats were studied. Oral consumption of food incorporated with seed powder significantly reduced serum glucose level on the 28th day (p